2022
DOI: 10.1021/acsaelm.2c00608
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Si-Doping on 45 nm Thick Ferroelectric ZrO2 Films

Abstract: In the last decades, ferroelectricity has been discovered in Si-doped HfO 2 and Hf 1−x Zr x O 2 thin films, and the origin of ferroelectricity is considered to be the presence of the polar Pca2 1 orthorhombic phase. Recently, some investigations suggest that ZrO 2 thin films show ferroelectric behavior as well. As a well-known dopant capable of modulating ferroelectricity in HfO 2 thin films, Si-doping is applied up to approximately 5.3% to modify the ferroelectric properties of ZrO 2 films in this work. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…For instance, the diluted magnetism could only appear in the t-phase for undoped ZrO 2 thin films [22]. Recently, the ferroelectricity has also been studied in ZrO 2 films [23][24][25]. For instance, Silva et al [23] reported an unprecedented ferroelectric structure in pure ZrO 2 thin films, opening up a new route to ferroelectric devices using Zr-rich HZO.…”
Section: Introduction mentioning
confidence: 99%
“…For instance, the diluted magnetism could only appear in the t-phase for undoped ZrO 2 thin films [22]. Recently, the ferroelectricity has also been studied in ZrO 2 films [23][24][25]. For instance, Silva et al [23] reported an unprecedented ferroelectric structure in pure ZrO 2 thin films, opening up a new route to ferroelectric devices using Zr-rich HZO.…”
Section: Introduction mentioning
confidence: 99%
“…Here, the 10 nm ZrO 2 thin films are thinner and deposited with a different ALD tool, which might lead to a different impact of the ozone dose time on the film properties, but still, a longer ozone dose time leads to a lower in-plane tensile stress. The lower biaxial in-plane tensile stress is considered to be an important factor in stabilizing the m-phase. ,,,, Surface energy is described as another critical factor influencing ferroelectric behavior. Since surface energy cannot be directly characterized, changes in the grain size are typically discussed. , Figure d exhibits the grain size and surface roughness with various ozone dose times.…”
Section: Resultsmentioning
confidence: 99%
“…In polycrystalline HZO-based thin films, the origin of ferroelectricity is commonly reported to be from a non-centrosymmetric orthorhombic phase with a space group of Pca2 1 . ,,, However, the fluorite-structured thin films typically have a polymorphic structure, and the non-polar P2 1 /c monoclinic phase and P4 2 /nmc tetragonal phase may be present in the film at the same time. , Compared to the m-phase, the t-phase can exhibit a reversible electric field-induced phase transition to the ferroelectric o-phase, which is considered one of the origins of antiferroelectric behavior in the ZrO 2 thin films. , As a fluorite-structured material like HfO 2 , undoped polycrystalline ZrO 2 thin films remain relatively understudied due to the loss of ferroelectricity . However, the ferroelectric behavior in the undoped ZrO 2 films has been reported recently, especially in films thicker than 20 nm where the ferroelectric behavior is suppressed in HZO since the m-phase is stabilized . Therefore, further insight into stabilizing ferroelectricity in ZrO 2 films is important for developing ferroelectric and pyroelectric CMOS-compatible devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following on from the numerous works on HfO 2 and doped HfO 2 , pure films of ZrO 2 [11,12] have also been found to be ferroelectric, although there has been less focus on this material, to date. For instance, Bohan et al have shown ferroelectric behaviour in polycrystalline 45 nm thick ZrO 2 films prepared by atomic layer deposition on TiN electrodes [32]. However, very recently, ferroelectricity was observed in ultrathin polycrystalline ZrO 2 films grown on Si with a thickness of only 5 Å [33].…”
Section: Introductionmentioning
confidence: 99%